Heavy Fermion Superconductivity and Antiferromagnetic Ordering in CePt3Si without Inversion Symmetry - Bauer, E. (2007)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Laboratorio de Bajas Temperaturas; Argentina